ETHNOGRAPHIC APPROACH TO EFL/ESL RESEARCH - Nikolaus Pasassung (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This article shows that ethnography, as an approach, is a very useful tool to be applied in research attempting a good understanding of EFL/ESL classrooms. With reference to work done by anthropologists and classroom researchers, the pre- sent article argues that education, including EFL/ESL classrooms, can be well un- derstood by using ethnographic  approaches.  This is done by elaborating  the rele- vance of ethnography and the classroom context in the sense that ethnographic prin- ciples are applicable in describing and understanding the culture of a classroom, and EFL/ESL teaching in particular.